The social problems of kidney failure patients and the role of social service in facing them - Al Shahrani, Ayedh bin Saad; Al Otaibi, Jaber; Al Jahni, Abdulrahman bin Jameel (Journal of Humanities & Social Sciences, 2017)
The study aimed to identify the problems faced by renal failure patients and the role of social service in confronting them. The researcher used the comprehensive social survey method in a comprehensive inventory of social workers, 32 specialists in Prince Mohammed bin Abdulaziz Hospital, King Saud Medical City, King Salman Center for Nephrology, The study used the intentional sampling method for patients with renal failure (60) patients representing the patients who regularly attend the King Saud Center for Kidney and the largest dialysis center in the Middle East.The results of the study showed that the problems faced by patients with renal failure were the most important from the point of view of the patients themselves and from the point of view of social workers is the difficulty of obtaining a kidney transplant, and not feeling safe. As for the problems faced by patients with their families, both sides agree that the most important problems faced by patients are weak social support from the family, but the least severe is the difficulty of communicating with family members during hospital stay. The problems facing the patients in their work also agreed on both sides that the most important of these problems is the inability of the patient to continue to work and the lack of appreciation of the owners of the nature of the patients, as for the problems facing the patient with friends and relatives and Jerth is not to involve the patient in social events, Some relationships break down as a result of the disease. As for the role of social service in dealing with these problems, the most important of these roles from the point of view of specialists is to assist the rehabilitation of the patient to be a human being together in his social interaction with the family and society. The results also indicated a study of cases of patients with psychological and social problems, , Contact the officials of the work to provide them with the regulations and laws on the work of patients, to guide friends not to talk about the disease to respond to the sense of lack, either from the point of view of patients was the most important roles of social service in the face of these problems are the most important assistance specialist To the patient in obtaining financial assistance from government agencies, and to facilitate administrative procedures for the patient.
Keywords: renal failure; social work; social problems